Prestige Pricing Strategy as A Symbol of Social Class on Perfume Products - NYOMAN S. SUBAWA (Jurnal Bisnis Manajemen, 2016)
Determination of the appropriate pricing strategy is essential in order to maintain and win the competition. This research examined the meaning of the application of the pricing strategy, especially prestige pricing for consumers who consume the product perfume in the city of Denpasar. The method used in this research is a qualitative method, by using descriptive analysis of qualitative and interpretative. The results showed that the first, the meaning of social class, that class was connected with the premium class perfume consumed by certain groups of people. Secondly, life style that is now for people using branded perfume is part of daily activities, and become part of the lifestyle. Because it was done patterned, repetitive, and in a certain period of time in accordance with the nature of the lifestyle itself. Third,are the value Psychological pricing, it was very specific in contrast to sales of other products in general. Producers to sellers maintain sales strategy accompanied with high price remain optimal service to attract or retain customers. Fourth, was the meaning of prestige, that the practice of buying branded perfume with an expensive price to increase or maintain the prestige of its users. Exchange of capital was very evident, buyers exchanging economic capital, social and cultural symbolic capital to achieve the sense of pride and prestige. In this research, the expected contribution is to interpret the application of prestige pricing strategy that so far only examined as part of the marketing strategy and consumer behavior.